Information system for assessing and monitoring patients with fibromyalgia syndrome – multidisciplinary approach. - Camargo, Rachel Schettert de; Moser, Auristela Duarte; Bastos, Laudelino Cordeiro; Moro, Claudia Maria Cabral (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Fibromyalgia Syndrome (FMS) is characterised by chronic widespread pain and tender points on palpation. FMS is associated with depression, anxiety, fatigue, sleep disorders, and functional bowel disorders that can intensify painful feelings, altering functional capacity and quality of life. The health provider usually identifies these conditions through assessment and monitoring tools and recordsthe results on paper. Failure to use electronic information systems, which have specific methodology for the integration of Health Information Systems, hampers the applicability of these methods in clinical practice and does not allow visualisation and comparison of the results in a simple manner. Objective: To propose an information system for assessing and monitoring patients with FMS (SISFIBRO). Method: The first phase consisted of data collection to select evaluation and monitoring methods used by doctors, physical therapists, rheumatologists, and specialists in fibromyalgia. Next, we performed the modelling of the system in the Unified Modelling Language (UML). Based on the diagram of classes, we performed conceptual data modelling with entity-relationship diagrams. The prototype was implemented with the SISFIBRO Oracle database. Below, we included data from 36 patients with FMS to analyse whether the system provided all of the information and necessary functions. Results: In Brazil, most of the professionals (82.4%) record and store patient data on paper charts, and 17.6% do so using electronic systems. The most widely used instruments and methods arethe visual analogue scale (VAS) SF-36, theFibromyalgia Impact Questionnaire (FIQ), evaluation of tender points according to the American College of Rheumatology (ACR), and the Beck Depression Scale; all are available in SISFIBRO. We developed 1 diagram of use, 1 diagram of classes, 6 diagrams of objects, and 5 diagrams of sequences. We decided that SISFIBRO must be integrated with the Electronic Health Record (EHR) for the recording, storing, sharing, and retrieving of the information. This integration will assist in the clinical practice of health professionals. Conclusion: It was possible to create a system with the reliability needed to support and improve the assessment and treatment of FMS.